2017
DOI: 10.1097/mjt.0000000000000346
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Effectiveness of PFNA, PFLCP, and DHS in Treatment of Unstable Intertrochanteric Femoral Fracture

Abstract: In this study, a randomized trial was conducted to compare the clinical effectiveness of proximal femoral locking compression plate (PFLCP), dynamic hip screw (DHS), and proximal femoral nail antirotation (PFNA) for unstable intertrochanteric femoral fracture treatment. Ninety patients diagnosed with unstable intertrochanteric femoral fracture were enrolled in this study at the department of orthopedics at Linyi Second People's Hospital between May 2010 and May 2012. Fractures were classified according to Tron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 21 publications
1
37
2
Order By: Relevance
“…A graph and summary of selection bias, performance bias, detection bias, attrition bias, reporting bias, and other biases identified in each RCT are shown in Figures 2 and 3. The randomization technique was not mentioned in 3 trials, [22,26,32] and the information of allocation concealment was not provided for 7 studies. [2226,29,32] The term “blinding of outcome assessment” was assessed as “high risk” for 15 studies owing to no difference in the postoperative radiological data between the 2 groups.…”
Section: Resultsmentioning
confidence: 99%
“…A graph and summary of selection bias, performance bias, detection bias, attrition bias, reporting bias, and other biases identified in each RCT are shown in Figures 2 and 3. The randomization technique was not mentioned in 3 trials, [22,26,32] and the information of allocation concealment was not provided for 7 studies. [2226,29,32] The term “blinding of outcome assessment” was assessed as “high risk” for 15 studies owing to no difference in the postoperative radiological data between the 2 groups.…”
Section: Resultsmentioning
confidence: 99%
“…During internal fixation of DHS, hip screws anchor less sclerotin and have a poor antirotation effect, resulting in prolonged operation time and increased intra-operative bleeding volume. Poor osteoarticular blood supply affects late recovery, which is likely to delay the healing process ( 8 , 9 ). Therefore, DHS fixation is not applicable in patients with severe osteoporosis or comminuted fracture in the lateral cortical bone of the femoral trochanter ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…This rate was reported to be 1.5% and 2.6% and 3.6% in studies by Zhang and Chan and Setibudy, respectively [16].…”
Section: Screw Cutout and Device Failurementioning
confidence: 95%
“…Zhang et al showed 1.5%; Qiang et al 2.6%; Setiobudi et al 3.6% device failure in their patients [16].…”
Section: Screw Cutout and Device Failurementioning
confidence: 99%